Effects of Using Graphic Calculators in the Teaching and Learning of Mathematics on Students’ Performance and Metacognitive Awareness - Mohd. Tajudin, Nor’ain (2008)
Three phases of quasi-experimental study with non-equivalent control group posttest only design were conducted to investigate the effects of using graphing calculators in mathematics teaching and learning on Form Four Malaysian secondary school students’ performance and their level of metacognitive awareness. Experiment in Phase I was conducted for two weeks to provide an initial indicator of the effectiveness of graphing calculator strategy on students’ performance and their metacognitive awareness. Graphing calculator strategy refers to the use of TI-83 Plus graphing calculator in teaching and learning of Straight Lines topic. The first phase involved one experimental group (n=21) and one control group (n=19) from two Form Four classes in a randomly selected school in Selangor. The experimental group underwent learning using graphing calculator while the control group underwent learning using conventional instruction. Experiment for Phase II was further carried out for six weeks incorporating measures of mathematical performance, focused on metacognitive awareness during problem solving and in addition, measures of mental effort and instructional efficiency. This phase involved two experimental groups (n=33) and two control groups (n=32) from four Form Four classes in one randomly selected school in Malacca. As in Phase I, the same learning conditions were given for both experimental and control groups. Finally, experiment in Phase III was carried out for six weeks incorporating comparison on two levels of mathematics ability (low and average) and two types of instructional strategy (graphing calculator strategy and conventional instruction strategy). Form Four students from one of schools in Malacca were the sample for Phase III. Altogether there were four groups of students given four learning conditions vis-à-vis: the average mathematical ability given the use of graphing calculators (n=15), the low mathematical ability also given graphing calculators (n=19), the average mathematical ability given the conventional instruction (n=16) and the low mathematical ability given also the conventional instruction (n=20).Four instruments were used in this study namely, Straight Lines Achievement Test, Paas Mental Effort Rating Scale, Metacognitive Awareness Survey and Graphing Calculator Usage Survey. The data for Phases I and II were analysed using independent t-test and planned comparison test while data for Phase III were analysed using multiple analysis of variance and planned comparison test. The study shows that the graphing calculator instruction enhanced students’ performance and induced higher levels of their metacognitive awareness with less mental effort invested during the learning and test phases and hence increased 3-dimensional instructional efficiency index in learning of Straight Lines topic for both groups of low and average mathematics ability. These findings indicated that the graphing calculator instruction is superior in comparison to the conventional instruction, hence implying that integrating the use of graphing calculator in teaching and learning of mathematics was more efficient than the conventional instruction strategy. The average mathematics ability group benefited more from the graphing calculator instruction as it decreased the amount of mental effort by double than the low mathematics ability group. Further, most students in graphing calculator strategy group showed an overall favourable view towards integrating the use of the graphing calculator in the teaching and learning of mathematics. Even though some students experience difficulties in using graphing calculators initially during learning, they responded overwhelmingly that graphing calculator improves their understanding of the Straight Lines topic and hence, the usage of the graphing calculator was an effective strategy in teaching and learning of mathematics.